2015
DOI: 10.1186/s12933-015-0215-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety of linagliptin in type 2 diabetes: a comprehensive patient-level pooled analysis of prospectively adjudicated cardiovascular events

Abstract: BackgroundThe cardiovascular (CV) safety of linagliptin was evaluated in subjects with type 2 diabetes (T2DM).MethodsPre-specified patient-level pooled analysis of all available double-blind, randomized, controlled trials, ≥12 weeks’ duration (19 trials, 9459 subjects) of linagliptin versus placebo/active treatment. Primary end point: composite of prospectively adjudicated CV death, non-fatal myocardial infarction, non-fatal stroke, and hospitalization for unstable angina (4P-MACE). Hospitalization for congest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 43 publications
5
67
1
1
Order By: Relevance
“…In a pooled analysis of randomized trials in T2DM patients comparing linagliptin to either placebo or an active comparator medication, linagliptin was not associated with an increased CV risk (37). The 27% increased risk of HF hospitalization with the DPP-4 inhibitor saxagliptin as observed in the SAVOR-TIMI 53 trial was not replicated in the EXAMINE or the TECOS trials with alogliptin and sitagliptin, respectively (38).…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pooled analysis of randomized trials in T2DM patients comparing linagliptin to either placebo or an active comparator medication, linagliptin was not associated with an increased CV risk (37). The 27% increased risk of HF hospitalization with the DPP-4 inhibitor saxagliptin as observed in the SAVOR-TIMI 53 trial was not replicated in the EXAMINE or the TECOS trials with alogliptin and sitagliptin, respectively (38).…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Although the DPP-4 inhibitors extend the actions of endogenous incretins, they appear to have diverse actions on other inflammatory and metabolic pathways which could have negated the CV protective role of prolonging GLP-1 activity. However, DPP-4 inhibitors were proven to be safe from a CV standpoint based on the available recent data despite concerns regarding increased HF risk prompting the issue of FDA warnings (30,32,33,(36)(37)(38).…”
Section: Update On Pioglitazonementioning
confidence: 99%
“…The DPP-4 inhibitors, otherwise known as the gliptins, are generally considered to have a neutral effect on weight. 58,59 Cardiovascular safety…”
Section: Dipeptidyl Peptidase-4 Inhibitors (Dpp-4 Inhibitors)mentioning
confidence: 99%
“…120 Another recent study has suggested that, according to a pooled analysis of trials, linagliptin is not associated with increased CV risk versus active comparators or placebo in patients with T2DM. 121 Currently there are other ongoing randomized clinical trials comparing DPP-4i versus placebo added to conventional therapy in patients with T2DM. The CArdiovascular safety and renal microvascular outcomE study with LINAgliptin in patients with T2DM (CARMELINA), lasting till 2018, has been designed to assess the long-term impact on CV morbidity, mortality and renal function of treatment with linagliptin.…”
Section: Cardiovascular Safety Of Dpp-4 Inhibitors: Evidence From Stumentioning
confidence: 99%